2017
DOI: 10.1016/j.gaitpost.2017.03.035
|View full text |Cite
|
Sign up to set email alerts
|

High-heeled walking decreases lumbar lordosis

Abstract: An estimated 78% of women regularly walk in high heels. However, up to 58% complain about low back pain, which is commonly thought to be caused by increased lumbar lordosis. However, the extent to which a subject's posture is modified by high-heeled shoes during dynamic activities remains unknown. Therefore, we sought to evaluate whether low- or high-heeled shoes influence the kinematics of the pelvis and the spine during walking. Twenty-three inexperienced women, and seventeen women experienced in wearing hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 20 publications
5
21
0
1
Order By: Relevance
“…In accordance with previous studies [1], [15], significant differences were observed as a result of HH wearing -lumbar lordosis was straightened. Lumbar as well as cervical lordosis were decreased with statistical significance in HH.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with previous studies [1], [15], significant differences were observed as a result of HH wearing -lumbar lordosis was straightened. Lumbar as well as cervical lordosis were decreased with statistical significance in HH.…”
Section: Discussionsupporting
confidence: 93%
“…In HH, the pressure force was shifted forward and increased the forefoot pressure, which corresponds with other studies [4], [11], [30]. It indicates that a weight transfer mechanism is triggered by HH [1].…”
Section: Discussionsupporting
confidence: 87%
“…Thus, wearing shoes with higher heels (up to a point) might indirectly help to compensate for inadequate hip extension, decreasing pain and leading to fewer pain exacerbations. However, an important caveat to this theory is that there is significant variability between studies, with many reporting that high-heeled (>4 cm) walking showed a decrease or no change in lumbar lordosis [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The standing trial was used as a basis to compute the relative positions of the two segments. For the spine, a segmental [31] and curvature approach [31,35,36] was used, and the curvature angle [37] was calculated.…”
Section: Data Processing and Analysismentioning
confidence: 99%